Active vision gates ocular dominance plasticity in human adults - Steinwurzel, Cecilia; Morrone, Maria Concetta; Sandini, Giulio; Binda, Paola (Current biology, 2023)
Primary visual cortex (V1) retains a form of plasticity in adult humans: a brief period of monocular deprivation induces an enhanced response to the deprived eye, which can stabilize into a consolidated plastic change1,2 despite unaltered thalamic input3. This form of homeostatic plasticity in adults is thought to act through neuronal competition between the representations of the two eyes, which are still separate in primary visual cortex4,5. During monocular occlusion, neurons of the deprived eye are thought to increase response gain given the absence of visual input, leading to the post-deprivation enhancement. If the decrease of reliability of the monocular response is crucial to establish homeostatic plasticity, this could be induced in several different ways. There is increasing evidence that V1 processing is affected by voluntary action, allowing it to take into account the visual effects of self-motion6, important for efficient active vision7. Here we asked whether ocular dominance homeostatic plasticity could be elicited without degrading the quality of monocular visual images but simply by altering their role in visuomotor control by introducing a visual delay in one eye while participants actively performed a visuomotor task; this causes a discrepancy between what the subject sees and what he/she expects to see. Our results show that homeostatic plasticity is gated by the consistency between the monocular visual inputs and a person’s actions, suggesting that action not only shapes visual processing but may also be essential for plasticity in adults. Steinwurzel et al. measured eye dominance after delaying vision to one eye during an active motor task and found similar changes of ocular dominance observed during contrast deprivation, indicating that action can reopen homeostatic plasticity of early visual cortex.